Development of Interactive PopUp Book Media to Increase the Interest in Learning SKI of MTs Students - Silvia Alvinatus Saadah; Muhammad Sugianto; Abd. Hannan (CV. Edujavare Publishing, 2026)
Education is an important aspect of human life that plays a role in shaping the quality of human resources. This study aimed to develop an interactive Pop Up Book learning media on the Khulafaur Rasyidin material, determine its feasibility, and examine its effectiveness in increasing students' learning interest. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were 17 seventh-grade students of MTs Miftahul Ulum Jrebeng Kulon Kedopok Probolinggo. Data were collected through observation, interviews, documentation, questionnaires, and learning achievement tests. The results showed that the developed Pop Up Book media obtained a validation score of 100% from both material and media experts, indicating a very feasible category. Student responses reached 79%, which was categorized as good. Furthermore, the average pretest score increased from 65 to 79 in the posttest. The N-Gain score was 0.40, which falls into the moderate category. These findings indicate that the developed Pop Up Book media is feasible and sufficiently effective in improving students' learning interest and learning outcomes in Islamic Cultural History learning.